Hubungan perdagangan antara Singapura dengan Asia Barat: Peranan Gulf Cooperation Council, 1981-2013 / Tan Chew Yi - Tan, Chew Yi (2016)
This research studies the relationship between Singapore and West Asia, particularly the role of Gulf Cooperation Council (GCC), between 1981 and 2013, by looking into trade relationship established through trade missions, areas of coorporation, agreements sealed and trade statistics during the era of each Prime Minister of Singapore i.e. Lee Kuan Yew, Goh Chok Tong and Lee Hsien Loong. For this research, there are three objectives. The first objective of this study is to explain the history of early trade between Singapore and West Asia before the establishment of GCC in year 1981. Next, to study the pattern and changes in trade mission between Singapore and West Asia, especially GCC during the era of Lee Kuan Yew, Goh Chok Tong and Lee Hsien Loong. Lastly, to analyse trade cooperation between Singapore and West Asia, especially GCC, during the era of Lee Kuan Yew, Goh Chok Tong and Lee Hsien Loong. Library research method is used throughout the study. Primary sources used include newspaper, news, press release, occasional report, speech, agreement and statistical record while secondary sources used include book, article, conference working paper and dissertation. Sources used are obtained from the University of Malaya Libary, the National Library Singapore, website of the National Archives of Singapore, website of the Singapore Department of Statistics and other relevant sources. This research highlights the close trade relationship between Singapore and West Asia, particulary GCC. This is visible through the two-way trade missions between Singapore and GCC and also the number of trade agreements sealed especially during the administration of Lee Hsien Loong. Oil crisis and conflict in GCC does not hold back trade relationship between Singapore and GCC. Besides carrying out trade missions, Singapore has also exhibited Her products in GCC, promoted Halal foods produced by Singapore companies as well as shown Her talent in fields such as water technology, shipping and engineering in order to attract investors from GCC. Besides that, similarities between Singapore and GCC has also led to the cooperation between Singapore and GCC. The research also shows that Singapore stresses the importance of having GCC as one of Her most important trading partners. One significant incident is when Singapore, together with its Muslim minority group, ventured into Halal food industry.